PENGARUH INFLASI, KAPITALISASI PASAR DAN LIKUIDITAS PERUSAHAAN TERHADAP HARGA SAHAM PADA INDEKS LQ45 - Alifah Sajidah; Firda Alfi Ningtyas; Kevin Andrian; Firman David; Sarumaha Siska; Sunita Dasman (STKIP Subang, 2025)
The capital market is an aspect that influences economic progress in Indonesia. In the economic and financial fields, the capital market is a very important war in this field, because it is one of the sources of external funding for the business world and investment. The research method used is descriptive analysis (descriptive research design), and the correlational method includes describing the relationship between the variables studied and describing the effect of independent variables on the dependent variable. From the sample of 5 companies taken, it shows that banking companies in Indonesia listed on the LQ45 Index are in a healthy financial capacity. A healthy LDR is generally in the range of 80% -90%, which means that the company can use its funds efficiently to provide loans. Based on the analysis of this study, the banking sector included in the LQ45 index showed a fairly good financial condition during the observation period of 2019-2023. The results of the study obtained stated that market capitalization did not have a significant positive effect on stock prices, while inflation and liquidity calculated by the Loan to Deposit Ratio (LDR) did not have a significant negative effect on stock prices.